Role of neuroinflammation in the emotional and cognitive alterations displayed by animal models of obesity - Castanon, Nathalie; Luheshi, Giamal; Laye, Sophie (Frontiers in Neuroscience, 2015)
Obesity is associated with a high prevalence of mood disorders and cognitive dysfunctions in addition to being a significant risk factor for important health complications such as cardiovascular diseases and type 2 diabetes. Identifying the pathophysiological mechanisms underlying these health issues is a major public health challenge. Based on recent findings, from studies conducted on animal models of obesity, it has been proposed that inflammatory processes may participate in both the peripheral and brain disorders associated with the obesity condition including the development of emotional and cognitive alterations. This is supported by the fact that obesity is characterized by peripheral low-grade inflammation, originating from increased adipose tissue mass and/or dysbiosis (changes in gut microbiota environment), both of which contribute to increased susceptibility to immune-mediated diseases. In this review, we provide converging evidence showing that obesity is associated with exacerbated neuroinflammation leading to dysfunction in vulnerable brain regions associated with mood regulation, learning and memory such as the hippocampus. These findings give new insights to the pathophysiological mechanisms contributing to the development of brain disorders in the context of obesity and provide valuable data for introducing new therapeutic strategies for the treatment of neuropsychiatric complications often reported in obese patients.